Neurological Impairment Linked with Cortico-Subcortical Infiltration of Diffuse Low-Grade Gliomas at Initial Diagnosis Supports Early Brain Plasticity - Smits, Anja; Zetterling, Maria; Lundin, Margareta; Melin, Beatrice; Fahlström, Markus; Grabowska, Anna; Larsson, Elna-Marie; Berntsson, Shala Ghaderi (Frontiers in Neurology, 2015)
Diffuse low-grade gliomas (DLGG) are slow growing brain tumors that in spite of an indolent behavior at onset show a continuous expansion over time and inevitably transform into malignant gliomas. Extensive tumor resections may be performed with preservation of neurological function due to neuroplasticity that is induced by the slow tumor growth. However, DLGG prefer to migrate along subcortical pathways and white matter plasticity is considerably more limited than grey matter plasticity. Whether signs of functional decompensating white matter may be found as early as at disease presentation has not been systematically studied. Here we examined 52 patients who presented with a DLGG at the time of radiological diagnosis. We found a significant correlation between neurological impairment and eloquent cortico-subcortical tumor localization, but not between neurological function and tumor volume. These results suggest that even small tumors invading white matter pathways may lack compensatory mechanisms for functional reorganization already at disease presentation.